2008
DOI: 10.1002/j.2168-9830.2008.tb00978.x
|View full text |Cite
|
Sign up to set email alerts
|

Persistence, Engagement, and Migration in Engineering Programs

Abstract: Records from the Multiple‐Institution Database for Investigating Engineering Longitudinal Development indicate that engineering students are typical of students in other majors with respect to: persistence in major; persistence by gender and ethnicity; racial/ethnic distribution; and grade distribution. Data from the National Survey of Student Engagement show that this similarity extends to engagement outcomes including course challenge, faculty interaction, satisfaction with institution, and overall satisfact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
322
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 449 publications
(351 citation statements)
references
References 13 publications
6
322
3
Order By: Relevance
“…We examined whether self-efficacy and academic commitment predicts academic achievement within a self-regulatory framework and described whether identity-relevant commitment as imposes constraints on, and influences goal-and task-related commitments. Our study contributes to the growing literature on academic commitment (Human-Vogel, 2013;Human-Vogel & Rabe, 2015) and we hope to contribute to the national access-success debate in South African universities (Lewin & Mawoyo, 2014), as well as retention debates in other parts of the world such as the USA, Europe and Australia (Ohland et al, 2008;Wilcoxon et al, 2011;Van den Bogaard, 2012). The complex interplay between institutional, academic and non-academic factors that contribute to student success (Human-Vogel & Mahlangu, 2009) make it unlikely for any single study or intervention to offer definitive suggestions for solving the problem of student access and success (Lewin & Mawoyo, 2014).…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…We examined whether self-efficacy and academic commitment predicts academic achievement within a self-regulatory framework and described whether identity-relevant commitment as imposes constraints on, and influences goal-and task-related commitments. Our study contributes to the growing literature on academic commitment (Human-Vogel, 2013;Human-Vogel & Rabe, 2015) and we hope to contribute to the national access-success debate in South African universities (Lewin & Mawoyo, 2014), as well as retention debates in other parts of the world such as the USA, Europe and Australia (Ohland et al, 2008;Wilcoxon et al, 2011;Van den Bogaard, 2012). The complex interplay between institutional, academic and non-academic factors that contribute to student success (Human-Vogel & Mahlangu, 2009) make it unlikely for any single study or intervention to offer definitive suggestions for solving the problem of student access and success (Lewin & Mawoyo, 2014).…”
Section: Discussionmentioning
confidence: 69%
“…Retention figures for Europe and the United States reported by the Organisation for Economic Co-operation and Development (2004) remain steady at about 30%. Within the fields of science and engineering a study involving nearly 70 000 students using MIDFIELD data from nine institutions in the United States, retention of science and engineering students did not differ significantly from other majors (Ohland, Sheppard, Lichtenstein, Eris, Chachra, & Layton, 2008). They found that 57% of engineering students were still enrolled in engineering by the fourth semester.…”
Section: Introductionmentioning
confidence: 97%
“…Between 2009 and 2013, approximately, 22% of women compared with 29% of men intended to major in STEM (4,5). These numbers dwindle quickly in the first few semesters of college as many students switch out of STEM (6,7). In engineering, for example, 40% of students who initially intend to major in engineering switch majors (7).…”
mentioning
confidence: 99%
“…These numbers dwindle quickly in the first few semesters of college as many students switch out of STEM (6,7). In engineering, for example, 40% of students who initially intend to major in engineering switch majors (7). Even though women who initially intend to major in STEM tend to be wellqualified in terms of prior preparation in math and science (3,8), they often report less confidence and motivation to pursue STEM careers compared with male peers (9,10).…”
mentioning
confidence: 99%
“…One of the two most distinguishing characteristics of the engineering population is that it is "disproportionately male" 15 . While women persist in undergraduate engineering programs at the same rate as men, a lower percentage of women pursue engineering careers after graduation and those who do enter engineering careers are less likely to persist 16 .…”
Section: Importance Of Diversitymentioning
confidence: 99%